Academic Supervision Practices Integrated into the School Supervisor Support Programs: Teachers’ Point of View - Victorynie, Irnie; Othman, Azam Bin (International Journal of Asian Education, 2023)
Academic supervision stands out as a commendable initiative designed to aid and bolster teachers in executing their responsibilities within the school setting. Moreover, numerous challenges and hindrances faced by educators are tackled through the implementation of academic supervision activities. This research aims to explore teachers' experiences undergoing academic supervision and the supervisors' support to overcome teacher problems and improve their performance. Researchers used qualitative research methods with an exploratory case study approach. Data was obtained from semi-structured interviews. The informants were four teachers at two integrated Islamic elementary schools in Bekasi, Indonesia, who were selected based on their extensive experience in carrying out school academic supervision. The resulting data was analyzed thematically using Atlas.ti software. The findings reveal that academic supervision is incredibly beneficial for teachers. It does not only assess teacher performance but also helps teachers solve problems to improve teacher performance. Teachers also received many support programs to improve the quality of learning in their schools.